ANALISIS PENGENDALIAN KUALITAS CELANA OLAHRAGA DENGAN MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) PADA PT. SAMI GRUP PUTRYANS - Gerry Sastro; Mitha Hudriyah; Dewi Purnama Sari (Math Program, Math and Science faculty, Pamulang University, 2023)
The purpose of this study was to determine the level of damage that occurred and also to determine the factors that cause damage to the production. By using statistical aids in the form of check sheets, p control charts, histograms, and cause and effect diagrams. Starting with a check sheet to collect data to make it more neat and structured, the next step is to enter the data into histogram form to make it easier to present the data, then calculate using a p control chart to find out whether the damage is still within the control limits or not, then make a cause and effect diagram. to find out what factors cause damage to PT. Sami Putrians Group. The results of the analysis show that the damage is outside the control limits, this is shown in the results of the calculation of the damage with the criteria of dirty materials and missed stitches which still have points that are outside the UCL limit. The cause-and-effect diagram gives results regarding the factors that cause the most dominant damage, namely humans due to lack of thoroughness, lack of skills, lack of motivation, lack of firmness and lack of discipline, the second cause is material caused by the material used is below standard, the third is the environment because the environment is lacking comfortable and lack of lighting, the last is the engine factor because it is not carried out routine and appropriate maintenance on the machine used.Keywords: Check sheet, Diagram, Control chart.